HEALTH, FUNCTIONAL AND QUALITY OF LIFE OUTCOMES OF CREATINE SUPPLEMENTATION BEYOND ATHLETIC PERFORMANCE: A NARRATIVE REVIEW - Magdalena Franków; Anna Kudłacik; Kornel Adrian Jarosz; Aleksandra Karolina Schmidt; Aleksandra Regina Żmuda; Maria Całusińska-Skowron; Julia Łukasik; Klaudia Jeziorowska; Karolina Bałdys; Oktawian Kaczmarek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Creatine supplementation is one of the most effective nutritional strategies for improving athletic performance and increasing skeletal muscle mass. Recently, interest has expanded toward its potential benefits in health promotion, aging, rehabilitation, metabolic health, and quality of life. Aim: This narrative review summarizes current evidence on the effects of creatine supplementation beyond sports performance, with emphasis on physical function, muscle health, metabolic and cognitive outcomes, and quality of life. Methods: A literature search was conducted in April–May 2026 using PubMed, Scopus, Web of Science, Google Scholar, and other relevant databases. Keywords included “creatine supplementation,” “aging,” “sarcopenia,” “cognition,” “metabolic health,” and “quality of life.” Priority was given to systematic reviews, meta-analyses, randomized controlled trials, and position stands in English. Results: Evidence suggests that creatine supplementation improves muscle strength, lean body mass, exercise capacity, and functional performance, especially when combined with resistance training. Benefits are also observed in older adults with sarcopenia. Emerging data indicate possible positive effects on cognitive performance, mental fatigue, metabolic health, and neurological function. Creatine appears safe in healthy individuals at recommended doses. Conclusions: Creatine supplementation may provide benefits beyond sports performance, particularly for muscle health, physical function, and quality of life. However, further long-term randomized controlled trials are needed to confirm clinical effects in non-athletic populations.